2017
DOI: 10.3389/fimmu.2016.00671
|View full text |Cite
|
Sign up to set email alerts
|

Factor H Binds to Extracellular DNA Traps Released from Human Blood Monocytes in Response to Candida albicans

Abstract: Upon systemic infection with human pathogenic yeast Candida albicans (C. albicans), human monocytes and polymorph nuclear neutrophilic granulocytes are the first immune cells to respond and come into contact with C. albicans. Monocytes exert immediate candidacidal activity and inhibit germination, mediate phagocytosis, and kill fungal cells. Here, we show that human monocytes spontaneously respond to C. albicans cells via phagocytosis, decondensation of nuclear DNA, and release of this decondensed DNA in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 52 publications
(56 reference statements)
7
67
0
Order By: Relevance
“…For instance, Bonne-Année et al [32] noted that although human monocyte-derived macrophages produced METs in response to Strongyloides stercoralis infection, mouse peritoneal macrophages did not, despite the fact that both human and mouse neutrophils produced NETs during infection. Similarly, Schorn et al [10] reported that neutrophils, basophils, and eosinophils responded to monosodium urate crystals in gouty arthritis [22] were not able to demonstrate similar responses with human peripheral-blood monocytes. Current evidence is insufficient to determine if the differential responses are due to experimental conditions or if some types of macrophages are inherently more prone to METosis.…”
Section: Noted Thatmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Bonne-Année et al [32] noted that although human monocyte-derived macrophages produced METs in response to Strongyloides stercoralis infection, mouse peritoneal macrophages did not, despite the fact that both human and mouse neutrophils produced NETs during infection. Similarly, Schorn et al [10] reported that neutrophils, basophils, and eosinophils responded to monosodium urate crystals in gouty arthritis [22] were not able to demonstrate similar responses with human peripheral-blood monocytes. Current evidence is insufficient to determine if the differential responses are due to experimental conditions or if some types of macrophages are inherently more prone to METosis.…”
Section: Noted Thatmentioning
confidence: 99%
“…Yousefi et al [9] described DNA release from eosinophils within 5 min of stimulation with complement component C5a or lipopolysaccharide (LPS), and the maximum effect, measured as fluorescence of a cell-impermeable DNA-staining dye, occurred within 30 min. METosis has been described as a rapid process that can occur in <30 min [22,23].…”
Section: Defining and Identifying Metsmentioning
confidence: 99%
See 3 more Smart Citations